Visualization of Business Process Modeling Anti Patterns - Laue, Ralf; Awad, Ahmed (Electronic Communications of the EASST, 2010)
Patterns are used to capture and document frequent design activities. Patterns are means to compare the expressiveness of different modeling languages. On the other hand, the term anti-pattern points to undesirable design activities. In the field of business process modeling, useful patterns were collected to help evaluate models and tools. Nevertheless, there was almost no work to capture the unwanted design patterns. The most common way to model business processes is to use a graphical modeling language. The most widespread notation are business process diagrams modeled in the language BPMN. In this paper, we formalize structural patterns that can lead to control flow errors in such graphical models. For expressing such error patterns, we use the visual query language BPMN-Q . By using a query processor, a business process modeler is able to identify possible errors in business process diagrams. Moreover, the erroneous parts of the business process diagram can be highlighted when an instance of an error pattern is found. This way, the modeler gets an easy-to-understand feedback in the visual modeling language he or she is familiar with.